1996
DOI: 10.1152/ajpgi.1996.270.1.g128
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to fat markedly increases pancreatic secretory response to intraduodenal fat in rats

Abstract: Exposure to higher levels of fat in the diet increases the secretion of fat-digesting enzymes in pancreatic juice. This study examines the functional consequences of this phenomenon and demonstrates that adapting rats to high fat (triglyceride) loads increases the release of cholecystokinin (CCK) and the pancreatic secretory response to intraduodenal fat. Lipolytic activity in the small intestine was also higher in adapted rats. Exchanging pancreatic juice from unadapted rats with pancreatic juice from adapted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
55
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 0 publications
2
55
1
Order By: Relevance
“…Our study corroborated the findings of previous investigations showing that infusion of SO or SBTI into the duodenum increases the levels of circulating CCK (42,50), although the basal circulating CCK concentrations observed in the present study were approximately twofold higher than those reported elsewhere. Others reported peak levels after SBTI (28,30) or SO (19) to be Ͻ11 pM compared with 20 pM observed in our laboratory.…”
Section: Discussionsupporting
confidence: 93%
“…Our study corroborated the findings of previous investigations showing that infusion of SO or SBTI into the duodenum increases the levels of circulating CCK (42,50), although the basal circulating CCK concentrations observed in the present study were approximately twofold higher than those reported elsewhere. Others reported peak levels after SBTI (28,30) or SO (19) to be Ͻ11 pM compared with 20 pM observed in our laboratory.…”
Section: Discussionsupporting
confidence: 93%
“…For example, Thomson et al (49) have previously shown that rats fed a high fat diet demonstrated an increase in the height of the villi and a 30% increase in the enterocyte migration rate without affecting the crypt cell production rate. Exposure to a high fat diet also resulted in significant increases in fat absorbability (50), the production and secretion of pancreatic lipases, as well as the ability of isolated rabbit enterocytes to secrete chylomicrons (51)(52)(53). Furthermore, rats fed a high fat diet showed a diminished satiation and reduced sensitivity to leptin (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…The physiologic importance of this dietary regulation has been shown. The up-regulation of PL enhances the response of cholecystokinin to increased dietary fat by increasing the rate of digestion of triglycerides and the release of FFAs in the proximal small intestine (17). In weanling animals, PL and PLRP1 adapt to increased dietary fat (41-75% of total energy) within 24 h. After 5 d, PL and PLRP1 reach higher steady-state levels of PL activity and synthesis and PL and PLRP1 mRNA (16 -22).…”
mentioning
confidence: 99%